“It Was Raining All the Time!”: Ex Post Tourist Weather Perceptions - Stefan Gössling; Bruno Abegg; Robert Steiger (Atmosphere, 2016)
The importance of weather for tourism is now widely recognized. However, no research has so far addressed weather events from retrospective viewpoints, and, in particular, the role of “extreme” events in longer-term holiday memories. To better understand the character of ex post weather experiences and their importance in destination image perceptions and future travel planning behavior, this exploratory study addressed a sample of 50 tourists from three globally important source markets: Austria, Germany and Switzerland. Results indicate that weather events do not dominate long-term memories of tourist experiences. Yet, weather events are important in shaping destination image, with “rain” being the single most important weather variable negatively influencing perceptions. Results also suggest that weather events perceived as extreme can involve considerable emotions. The study of ex post traveler memories consequently makes a valuable contribution to the understanding of the complexity of “extreme weather” events for tourist demand responses.